2021
DOI: 10.1101/2021.05.27.445689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of clustered mutations in cancer reveals recurrent APOBEC3 mutagenesis of ecDNA

Abstract: Clustered somatic mutations are common in cancer genomes with prior analyses revealing several types of clustered single-base substitutions, including doublet- and multi-base substitutions, diffuse hypermutation termed omikli, and longer strand-coordinated events termed kataegis. Here, we provide a comprehensive characterization of clustered substitutions and clustered small insertions and deletions (indels) across 2,583 whole-genome sequenced cancers from 30 cancer types. While only 3.7% of substitutions and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Extensive exploration of the aetiology of kataegis revealed a significant positive correlation between kataegis and two distinct mutational signatures both attributed to the APOBEC enzyme-family Alexandrov et al, 2020;Bergstrom, Luebeck, et al, 2022;Burns et al, 2013;Taylor et al, 2013b). Subsequently, multiple studies confirmed the importance of the APOBEC enzymes in cancer, showing that APOBEC is a major cause of mutagenesis, both seen in clusters, dispersed throughout the cancer genome and in extrachromosomal DNA (Bergstrom et al, 2021;Bergstrom, Luebeck, et al, 2022;Langenbucher et al, 2021;Maciejowski et al, n.d.;Taylor et al, 2013a). Previous studies have shown that kataegis occurs within known cancer genes including TP53, EGFR and BRAF which are associated with overall survival (Bergstrom, Luebeck, et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Extensive exploration of the aetiology of kataegis revealed a significant positive correlation between kataegis and two distinct mutational signatures both attributed to the APOBEC enzyme-family Alexandrov et al, 2020;Bergstrom, Luebeck, et al, 2022;Burns et al, 2013;Taylor et al, 2013b). Subsequently, multiple studies confirmed the importance of the APOBEC enzymes in cancer, showing that APOBEC is a major cause of mutagenesis, both seen in clusters, dispersed throughout the cancer genome and in extrachromosomal DNA (Bergstrom et al, 2021;Bergstrom, Luebeck, et al, 2022;Langenbucher et al, 2021;Maciejowski et al, n.d.;Taylor et al, 2013a). Previous studies have shown that kataegis occurs within known cancer genes including TP53, EGFR and BRAF which are associated with overall survival (Bergstrom, Luebeck, et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…Subsequently, multiple studies confirmed the importance of the APOBEC enzymes in cancer, showing that APOBEC is a major cause of mutagenesis, both seen in clusters, dispersed throughout the cancer genome and in extrachromosomal DNA (Bergstrom et al, 2021; Bergstrom, Luebeck, et al, 2022; Langenbucher et al, 2021; Maciejowski et al, n.d. ; Taylor et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%